Metamaterial Based Body Wearable Antennas and Applications- A Review - Singh, Jaget (International Journal of Computer Sciences and Engineering, 2019)
In this paper application of metamaterial has been discussed. Metamaterial is an artificial material which exhibits unique properties which cannot be achieved from the conventional materials. Metamaterial can be used as antenna substrate, feed networks, phased array antenna and antenna ground planes. Metamaterial can be used to increase the gain directivity and bandwidth of antenna. In body wearable antennas specific absorption rate (SAR) also can be reduce.